Using Lecture Method Plus Demonstration and exercise to Improve the Ability to Make Sentences Uses Mandarin Vocabulary - Lily Thamrin; Felicia Siou Hun; Lusi Lusi (Universitas Muhammadiyah Enrekang, 2024)
This research was carried out based on the results of observations of teachers who only use the lecture method in teaching Mandarin vocabulary, and there are still many students who still have difficulty understanding the meaning and use of vocabulary, as well as making sentences using Mandarin vocabulary. This research was conducted for finding out whether the lecture method plus demonstration and exersice could improve the ability of Immanuel II Sungai Raya Christian Vocational School students in making sentences using Mandarin vocabulary. Data collection in this research used experimental, observation, literature and test methods. This research was conducted by comparing the use of the lecture method for the control group and the lecture method plus demonstration and exercises for the experimental group. The final results of the research showed that the experimental group students were able to use Mandarin vocabulary in making sentences very well compared to the control group, and the control group students experienced more mistakes in making sentences compared to the experimental group.